2014
DOI: 10.1002/jnr.23388
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging reveals differential modifications to cytoplasmic dynein properties by phospho‐ and dephosphomimic mutations of the intermediate chain 2C S84

Abstract: Cytoplasmic dynein is a multi-subunit motor protein responsible for intracellular cargo transport toward microtubule minus ends. There are multiple isoforms of the dynein intermediate chain (DYNC1I, IC) which is encoded by two genes. One way to regulate cytoplasmic dynein is by IC phosphorylation. The IC-2C isoform is expressed in all cells and the functional significance of phosphorylation on IC-2C serine 84 was investigated using live cell imaging of fluorescent protein-tagged wild type IC-2C (WT) and phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Thr89 phosphorylation can also promote dynein binding to the kinetochore protein ZW-10, for dynein localization on kinetochore (Whyte et al, 2008), rather than to p150glued, a mediator for interaction of dynein with various organelles/cargos (Schroer, 2004). In addition, live-cell imaging of dynein composed of Ser84 phospho-mimetic/phospho-resistant mutants of DIC suggests that phosphorylation at DIC Ser84 modulates dynein motor activity (Blasier et al, 2014). Thus, phosphorylation within the serine-rich domain positively or negatively regulates dynein behaviors through stimulating/inhibiting dynein motor activity and/or the association of dynein with organelles/cargos.…”
Section: Ampk-mediated Ser81 Phosphorylation Of Dic Contributes To Dymentioning
confidence: 99%
“…Thr89 phosphorylation can also promote dynein binding to the kinetochore protein ZW-10, for dynein localization on kinetochore (Whyte et al, 2008), rather than to p150glued, a mediator for interaction of dynein with various organelles/cargos (Schroer, 2004). In addition, live-cell imaging of dynein composed of Ser84 phospho-mimetic/phospho-resistant mutants of DIC suggests that phosphorylation at DIC Ser84 modulates dynein motor activity (Blasier et al, 2014). Thus, phosphorylation within the serine-rich domain positively or negatively regulates dynein behaviors through stimulating/inhibiting dynein motor activity and/or the association of dynein with organelles/cargos.…”
Section: Ampk-mediated Ser81 Phosphorylation Of Dic Contributes To Dymentioning
confidence: 99%
“…Phosphorylation of IC-2C on S84 also decreased binding of p150 in the solid phase assay and this was proposed to be the basis for the disrupted membrane bounded organelle transport observed in vivo [47], but see also [53]. Live cell imaging of S84 phospho- and dephosphomimetic mutants suggests that neither of the two mutants inhibits dynein, rather they modulate dynein motor activity [54]. …”
Section: Introductionmentioning
confidence: 99%
“…Several phosphotransferases have been identified that regulate FAT by modifying functional specific motor protein subunits [ 60 63 ]. Among protein kinases tested in the isolated axoplasm preparation, casein kinase 2 (CK2) inhibited FAT with an inhibitory profile similar to that induced by PrP-FL and PrP 106-126 ( Fig 1B and 1C ) [ 27 ], prompting us to evaluate whether the inhibition of FAT induced by PrP-FL or PrP 106-126 was mediated by CK2.…”
Section: Resultsmentioning
confidence: 99%
“…Under normal physiological conditions, the concerted activity of kinases and phosphatases regulate FAT by controlling the functional activities of molecular motors [ 60 63 ]. Under pathological circumstances, misregulated signaling pathways can alter motor functions, leading consequently to altered FAT and dysfunctional synaptic transmission [ 26 28 , 36 , 39 , 48 , 67 , 71 , 73 , 74 , 87 , 89 , 102 108 ], harmful events that result in progressive synaptic dysfunction and dying back neuropathy.…”
Section: Discussionmentioning
confidence: 99%